Complement activation by in vivo neonatal and in vitro extracorporeal membrane oxygenation - Johannes Graulich; Joseph Sonntag; Monika Marcinkowski; Karl Bauer; Hans Kössel; Christoph Bührer; Michael Obladen; Hans T. Versmold (Mediators of Inflammation)
Complement activation during extracorporeal membrane oxygenation (ECMO) in newborns can be caused by both the underlying disease processes and by blood contact with the ECMO circuit. We investigated the relative importance of these mechanisms by measuring C3a, C5a and sC5b-9 before, during and after neonatal ECMO in six consecutive newborn patients using enzyme-linked immunoassay. In addition complement activation during in vitro ECMO with repeated flow of the same blood volume was measured using blood from healthy adult donors. C3a increased significantly in vivo after 1 h (from 1035 ± 193 to 1865 ± 419 μg/l) and in vitro ECMO (from 314 ± 75 to 1962 ± 1062 μg/l). C5a increased during ECMO without significant differences between in vivo and in vitro activation. In neonatal patients, sC5b-9 rose faster than in vitro, but the rapid increase was also significant for in vitro experiments (in vivo: from 328 ± 63 to 1623 ± 387 μg/l after 2 h; and in vitro: from 78 ± 32 to 453 ± 179 μg/l after 8 h). After this initial peak at 1-2 h, complement activation decreased gradually until 2-3 days after the initiation of ECMO. We conclude that in newborns the rapid activation of the complement system after the start of ECMO is predominantly caused by contact with artificial surfaces rather than the patient's underlying disease.